PELATIHAN PENYUSUNAN LAPORAN KEUANGAN YAYASAN MENGGUNAKAN PROGRAM AKUNTANSI ACCURATE PADA YAYASAN PTAJM - Marselinus Asri (BEGAWE: Jurnal Pengabdian Masyarakat, 2024)
The Atma Jaya Makassar Higher Education Foundation (PTAJM) is an entity that has a central role in providing educational services and assistance to the community in its area. In order to maintain openness and accountability in financial management, PTAJM initiated training in preparing financial reports using the Accurate accounting program. This training aims to assess the effectiveness of this training in increasing the capacity of management staff in preparing financial reports and its impact on the quality of the PTAJM Foundation's financial reports. By extracting information from pre- and post-training surveys as well as interviews with management staff, this research analyzes changes in staff knowledge, skills and attitudes after attending the training. In addition, this research also examines the improvements that occur in the accuracy, completeness, and regularity of financial reports after the implementation of the training. The results of this research provide a deeper understanding of the effectiveness of training in increasing the capacity of management staff and the quality of financial reports at the PTAJM Foundation. The implications of this research can be a basis for increasing transparency, accountability and efficiency in the financial management of similar institutions in the future